(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Worldwide, diabetes has become the most common cause of end-stage renal disease (ESRD), yet Swiss data are largely lacking. METHODS This observational study examined ESRD patients with diabetes mellitus (ESRD-DM) at end of 2009 and 2014. The prevalence and characteristics of ESRD-DM patients were collected in all dialysis facilities in the Canton of Vaud of Switzerland in 2009 and in 2014, and the 5-year mortality rate was assessed. RESULTS A total of 107 and 140 ESRD-DM patients underwent dialysis at end of 2009 and 2014, respectively. Within the 5-year period a total of 167 incidental ESRD-DM patients required dialysis, corresponding to an estimated incidental rate of 0.84/1000 person-years in the diabetic population. In 2009, all patients with ESRD-DM underwent haemodialysis, decreasing to 96.2% in 2014, with 3.8% on peritoneal dialysis. Age, sex, body mass index, type of diabetes, duration of diabetes, cause of ESRD, dialysis duration, dialysis frequency, vascular access, and glycosylated haemoglobin levels did not differ between 2009 and 2014. In 2014, macrovascular comorbidity was reported more often than in 2009, but not amputations. Haemoglobin level decreased significantly from 117.9 g/l to 112.3 g/l. Calcium-containing phosphate binder and angiotensin-converting enzyme inhibitor use significantly decreased, whereas iron therapy significantly increased with time. The 5-year mortality rate was 61.7%. Five-year survivors were significantly younger and had a higher body mass index. CONCLUSIONS The growing prevalence of ESRD-DM emphasises that prevention of chronic kidney disease and its progression should be a public health priority in Switzerland.